A randomized trial exploring mindfulness and gratitude exercises as eHealth-based micro-interventions for improving body satisfaction. (June 2019) - Fuller-Tyszkiewicz, Matthew; Richardson, Ben; Lewis, Vivienne; Linardon, Jake; Mills, Jacqueline; Juknaitis, Kerry; Lewis, Charlotte; Coulson, Kim; O'Donnell, Renee; Arulkadacham, Lilani; Ware, Anna; Krug, Isabel
Abstract: Despite theoretical arguments that brief app-based interventions could be a useful adjunct to longer traditional treatment programs, there has been limited evaluation of the acceptability, feasibility, and efficacy of these micro-interventions. In the present study, 247 women from the general population were randomly assigned to the intervention or wait-list control condition, and provided measurement of body satisfaction and related constructs (body image importance, confidence dealing with body image issues, eating pathology, and self-esteem) at baseline and 21-days (post-intervention). During the 21-day period, the treatment group received access to an eHealth platform containing a series of brief video activities (e.g., gratitude tasks, breathing, and relaxation) previously demonstrated in experimental studies to improve body satisfaction. Findings showed greater improvements in body satisfaction at post-intervention for the intervention group than the waitlist controls (Cohen's d  = .42). Use of the intervention content was associated with immediate increases in state-like body satisfaction ratings, and the magnitude of these in-the-moment improvements was predictive of greater post-intervention symptom improvement and retention ( p s < .05). However, the intervention did not produce change in constructs related to body satisfaction (Cohen's d ranged from 0.02 to 0.13). Overall, findings offer support for micro-interventions as a spot treatment for specific symptoms, and possible means to maintain engagement and motivation within a broader treatment program. Highlights: We evaluated efficacy and acceptability of a micro-intervention for body satisfaction. The content produced immediate symptom reduction at time of use and post-intervention. Attrition rates were high, suggesting need to augment with motivational content. Micro-interventions have potential as an adjunct to traditional therapies, such as CBT.